Analysis of the Final Energy Use by Sectors in City of Vidin - Kostova-Ivanova, Daniela (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
According to the initiative "The Covenant of Mayors for Climate and Energy (CoM)" and within the framework of the EU-funded "Positive Energy Areas Project", the Municipality of Vidin should establish a "Sustainable Energy and Climate Action Plan". The city’s sustainable energy development plans aim to reduce CO2 emissions by 40% up to 2030 and develop a comprehensive climate change adaptation strategy at the local level or integrate it into existing plans. The initiative envisages actions both for mitigating climate change and also for climate adaptation at the local level. This paper presents the results of the first part of the process for establishing the "Sustainable Energy and Action Plan of the Municipality of Vidin", including the assessment and calculation of the final energy use in the city by the different sectors. The research aims to present the main data sources necessary for СО2 emissions inventory at the city level and to process, validate, and analyze used statistical data for defining the final energy use by different sectors in one Bulgarian municipality. The purpose of this assessment is to determine final energy use by different sectors and by types of energy sources. The results from the analysis and evaluation of the final energy use in the sectors "Residential buildings", "Municipal buildings", "Industry", "Tertiary buildings", "Public lighting" and "Transport" will serve to conduct a baseline of CO2 emissions inventory, which is a part of the “Sustainable Energy and Climate Action Plan”. These results also could help the local authorities and key energy players to identify and implement the most suitable measures and actions for climate change adaptation and mitigation.